Jihad in the Vortex of Social Media: Mainstreaming Digital Ethics as the Basis for Islamic Moderation - Kurniawan, Rikza Syahrial; Irham, Ananda Salsabiila; Salimudin, Salimudin; Sahri, Iksan Kamil (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the meaning of jihad in the context of social media and explain how digital ethics can be used as a basis for promoting Islamic moderation in the digital space. The research method used is qualitative with a literature review of data sources from academic journals, scientific articles, and policy documents relevant to the themes of digital jihad, digital ethics, and Islamic moderation. The results show that the concept of digital jihad is a contemporary form of ijtihad that represents the struggle of Muslims to maintain the integrity of teachings and public morality on social media. Digital ethics is found to be the epistemological basis for the preaching of Islamic moderation, which emphasizes verification (tabayyun), justice ('adl), and communication etiquette (qaulan sadīdan). Thus, Islamic moderation in the digital age can only be realized through the integration of Islamic moral values, media literacy, and ethical awareness in online religious practices. Thus, constructive digital jihad can reduce conflict, strengthen ukhuwah (brotherhood), and uphold Islam Wasathiyyah on social media.